Population Dynamics Trough Metapopulation Models: When do Cyclic Patterns Appear? - Frederico, P.; Canziani, G.A. (Trends in Computational and Applied Mathematics, 2000)
We consider a theoretical ecosystem divided into an infinite number of identical patches and occupied by an ideal species without competitors.